1987
DOI: 10.1212/wnl.37.9.1558
|View full text |Cite
|
Sign up to set email alerts
|

McArdle's disease in two generations

Abstract: A 17-year-old boy had exercise-induced cramps and myoglobinuria. The mother had myalgia and weakness after exercise but the father was asymptomatic. Muscle biopsy was normal in the father but showed glycogen storage and absent or markedly decreased histochemical stain for phosphorylase in mother and son. Autosomal dominant McArdle's disease was considered likely, but biochemical studies showed that muscle phosphorylase activity was 0.6% of normal in the son, 20% in the mother, and 45% in the father, with corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Manifesting heterozygotes have been reported in the literature (Table 3), even before the genetics of the disease were known (Fattah et al 1970;Baksi et al 1977;Engel et al 1987;Schmidt et al 1987;Taylor et al 1987;Papadimitriou et al 1990;Manfredi et al 1993). Their symptoms were essentially triggered by exercise and included myalgia, cramps, early fatigue, and weakness, which is in accordance with our data (Table 3).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Manifesting heterozygotes have been reported in the literature (Table 3), even before the genetics of the disease were known (Fattah et al 1970;Baksi et al 1977;Engel et al 1987;Schmidt et al 1987;Taylor et al 1987;Papadimitriou et al 1990;Manfredi et al 1993). Their symptoms were essentially triggered by exercise and included myalgia, cramps, early fatigue, and weakness, which is in accordance with our data (Table 3).…”
Section: Discussionsupporting
confidence: 91%
“…The pattern of inheritance of this disease is autosomal recessive, although some cases of patients showing McArdle-like symptoms or signs despite having a pathogenic mutation in only one of the two PYGM alleles, the so-called manifesting heterozygotes, have been reported in the literature (Fattah et al 1970;Baksi et al 1977;Engel et al 1987;Schmidt et al 1987;Taylor et al 1987;Papadimitriou et al 1990;Manfredi et al 1993). In some studies, pseudo-dominant inheritance has been established (Chui and Munsat 1976;Wu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…9 Our data confirm that the mutation at codon 49 is the most common genetic defect associated with myophosphorylase deficiency, at least in the American population. However, when residual activity falls below a certain level, approximately 20% of normal, symptoms may become evident.…”
supporting
confidence: 82%
“…The occurrence of manifesting heterozygotes with McArdle disease has been a long lasting controversy that could have important implications in diagnosis and genetic counselling 1719. Andersen et al 19 showed that non-symptomatic heterozygotes for PYGM gene mutations had maximal oxidative capacities and peak lactate responses identical to control subjects, suggesting that they are not prone to develop symptoms of McArdle disease.…”
Section: Discussionmentioning
confidence: 99%